Life-safety disparity index: a comprehensive, valid, and reliable tool to assess Chinese people’s life-safety performance - Ge, Xiaoyue; Wu, De an; Shi, Xinming; Zhang, Junxiang; Jiang, Jinghui; Zhang, Bicheng; Wang, Hongguang (Frontiers in Public Health, 2025)
AimsIn order to accurately and quantitatively grasp the current situation and trend of Chinese people’s life-safety performance and to provide scientific basis and suggestions for the government, scientific research institutions, enterprises and the public to do a good job in life-safety protection.MethodsThe establishment process of life-safety disparity index (LDI) included six steps, including (i) concept building (ii) framework formulation; (iii) indicator selection; (iv) database building; (v) weight determination; and (vi) LDI scores calculation. The indicator scheme for LDI based on this framework was constructed after multiple rounds of panel discussions with our expert advisory committee. We adopted the Data envelopment analysis-Compromise planning (DEA-CP) model to determine the weights for each indicator and calculate score.ResultsThe weighted indicator scheme of LDI comprised 6 first-grade indicators, 21 s-grade indicators, and 65 third-grade indicators. According to the pilot analysis based on the data from 31 provinces of China mainland, the maximum value of LDI was 100.00, the minimum value was 54.75, and the maximum value was 1.83 times the minimum value. According to the score, China mainland was divided into 5 life-safety guarantee zones, including high security zone, medium to high security zone, medium security zone, low to medium security zone, and low security zone.ConclusionLDI, which has been strictly verified, would represent the world’s first assessment tool that builds a conceptual framework from the overall perspective of ensuring life-safety.